Constructing Peace Identity: Hiroshima's Diplomatic Role in Nuclear Disarmament - Mubin, Sayyidul; Ramadhan, Fahrizal Basanto (Journal of Paradiplomacy and City Networks, 2024)
This article focused on how Hiroshima created and managed its peace identity and transformed itself into a strong player within global nuclear disarmament diplomacy. Based on constructivist theory, which states that identity and interests are developed through social interaction and interpretation, the study examined how Hiroshima evolved from a city that suffered as a result of the atomic explosion to become a strong advocate for nuclear disarmament. The qualitative case study approach was supported by process tracing and document analysis, and findings showed three important areas of the diplomatic evolution of Hiroshima: firstly, the capacity to change from being a war victim to a victor advocating for peace-building strategies and memorial strategies; secondly, the creation of a wide range of diplomatic relations through Mayors for Peace and other international associations; and third, the promotion of the nuclear disarmament norm through advocacy, education, documentation of survivors’ stories, and the encouragement of the Treaty on the Prohibition of Nuclear Weapons. The results showed the potential for cities to establish and use specific diplomatic identities that help in the modification of governance, more so in cases where state-to-state diplomacy is ineffective. This work adds to the body of knowledge on how non-state actors influence the structure and constructivism of norms and identity in nuclear politics.